A microeletromechanical system optical switch with integrated fiber alignment capability [elecronic resource] - 361243 Leow, Cheah Wei (2008)
Thesis (Doktor Falsafah (Fakulti Kejuruteraan Elektrik)) - Universiti Teknologi Malaysia, 2008